Future Skills of Tertiary Students Required for Industry in the Eastern Special Development Zone of Thailand - Makmee, Pattrawadee (The Journal of Behavioral Science, 2023)
Future skills are critical for tertiary students who want to compete in the industrial world. On the other hand, some conventional educational institutions typically lack instruction in these skills. The purposes of this research were to develop a model of future skills and test its consistency with empirical data, and to establish guidelines for the development of the skills. An explanatory sequential mixed methods study was conducted in two phases. Quantitative data were collected from 1,135 students from 227 disciplines, using multistage random sampling and multilevel confirmatory factor analysis. Qualitative data were collected from ten key informants through in-depth interview content analysis. The results from the quantitative phase revealed that the skill-measurement model consisted of three factors and 11 components and consistent with the empirical data (x2 = 73.62, df = 56, x2/df = 1.31, p = .06, RMSEA = .02, CFI = 1.00, TLI = 1.00, SRMRW = .01, SRMRB = .07). The quantitative phase, moreover, supported the quantitative finding, and indicated that life and career skills were the most important skills in the future skills of tertiary students. For the components of life and career skills, flexibility and adaptability skills were the most important at student level, while productivity and accountability skills were the most important at discipline level. Therefore, the guidelines for developing the future skills of tertiary students should first focus on learning from actual working to adapt to the future working environment and the curriculum should ensure the need from the private sector and student’s accountability.